Experimental and Theoretical Investigation of the Molecular and Electronic Structure of N-Cyclohexyl-2-[5-(4-pyridyl)-4-(p-tolyl)-4H-1,2,4-tria-zol-3-ylsulfanyl]acetamide Dihydrate - Dincer, Muharrem; Ozdemir, Namik; Cetin, Ahmet; Keser, Tekin (Int Union Crystallography, 2009)
[Abstract Not Available]
Keywords: single-crystal X-ray diffraction; quantum mechanics; theoretical crystal calculations